2012
DOI: 10.4014/jmb.1206.06058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilute Alkali on Structural Features and Enzymatic Hydrolysis of Barley Straw (Hordeum vulgare) at Boiling Temperature with Low Residence Time

Abstract: This work was conducted to evaluate the effect of dilute sodium hydroxide (NaOH) on barley straw at boiling temperature and fractionation of its biomass components into lignin, hemicellulose, and reducing sugars. To this end, various concentrations of NaOH (0.5% to 2%) were applied for pretreatment of barley straw at 105 o C for 10 min. Scanning electron microscopy (SEM), atomic force microscopy (AFM), and Fourier transform infrared (FTIR) spectroscopy studies revealed that 2% NaOHpretreated barley straw expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…Haque et al . 48 reported that compared to raw WS (45.0%), the CrI of WS samples increased to 52.3%, 57.9%, 65.3%, and 71.5% after pretreatment with 0.5%, 1.0%, 1.5%, and 2.0% NaOH at 105 °C, and the reducing sugar yield increased from 45% to 78% with higher NaOH concentrations (1%, 1.5%, and 2.0%) and CrIs. The CrI of hot water-pretreated WS (50.4%) slightly increased compared to that of raw WS, and the conversion rate of cellulose was only to be 28.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Haque et al . 48 reported that compared to raw WS (45.0%), the CrI of WS samples increased to 52.3%, 57.9%, 65.3%, and 71.5% after pretreatment with 0.5%, 1.0%, 1.5%, and 2.0% NaOH at 105 °C, and the reducing sugar yield increased from 45% to 78% with higher NaOH concentrations (1%, 1.5%, and 2.0%) and CrIs. The CrI of hot water-pretreated WS (50.4%) slightly increased compared to that of raw WS, and the conversion rate of cellulose was only to be 28.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Alkali pretreatment at a high temperature breaks down lignin and hemicelluloses into soluble fragments and makes more cellulose exposed to enzymes. Barley straw pretreated with aqueous NaOH (0.5-2.0%) at 105°C for 10 min resulted in a maximum 84.8% removal of lignin and 79.5% removal of hemicelluloses, meanwhile, a maximum reducing sugar yield of 86.5% was achieved during the following enzymatic hydrolysis process (Haque et al, 2012).…”
Section: Alkali Pretreatmentmentioning
confidence: 99%
“…The depletion of fossil fuels has led to an increasing interest in the use of renewable and sustainable resources, such as agricultural waste for the production of alternative fuels like bioethanol [12][13][14]. Bioethanol is ethyl alcohol, the same type of alcohol that is used in alcoholic beverages, and it is most often used as a motor fuel, mainly as a biofuel additive for gasoline [32].…”
Section: Introductionmentioning
confidence: 99%